INVESTIGATION ON THE CHANGE OF TSH, FT3, FT4 HORMONE CONCENTRATION IN DEMENTIA PATIENTS - Nguyễn Thị, Việt; Nguyễn Thị Thái, An; Vũ Quang, Huy (Journal of 175 Practical Medicine and Pharmacy, 2023)
Background: Thyroid dysfunction is a common condition in the elderly. Many studies have shown that changes in hormone concentration of TSH, FT3, FT4 are related to the pathogenesis of Alzheimer disease and other types of dementia. Objectives: Investigation into the change in hormone concentration of TSH, FT3, FT4 in dementia patients including mild cognitive impairment (MCI) and Alzheimer disease (AD) compared with the non-dementia group. Object and method: A cross-sectional study performed on 224 patients divided into two groups. The study group consisted of 112 dementia patients (according to the DSM-V diagnostic criteria) and the control group with 112 non-dementia patients. TSH, FT3, FT4 concentrations was measured on patients in each group to find out the association with dementia. The research was conducted at the Memory and Dementia Unit, April 30 Hospital from November 2020 to May 2021. Results: The mean concentration of TSH in the dementia group was 1.40 ± 0.95 μIU/ml, which lower than the non-dementia group was 1.71 ± 0.94 (p=0.014). In the dementia group, the prevalence of decrease in TSH level was 8.9% and increase in FT4 level was 9.8%, compared with the non-dementia group was 1.8% (p=0.038) and 0.9% (p = 0.005), respectively. More specific, in the MCI group, the mean concentration of TSH was 1.32 ± 0.47 μIU/ml, which lower than the non-dementia group was 1.71 ± 0.94 μIU/ml (p = 0.025). In the AD group, the mean concentration of FT4 was 0.92 ± 0.18 ng/dL, which higher than the non-dementia group was 0.89 ± 0.11 ng/dL (p < 0.001). Conclusion: This study has found that generally the dementia patients had higher FT4 and lower TSH levels than the non-dementia patients. The concentration of TSH in the MCI patients was lower than the non-dementia patients and the concentration of FT4 in the AD patients was higher than that levels in the non-dementia patients.